Implementasi Aplikasi E-Manajemen Penyidikan Guna Meningkatkan Kinerja Penyidik - Dyanita Shafira (Indonesian Journal of Police Studies, 2020)
This research is motivated by the demands of investigators in the digital era relating to criminal investigation activities, especially in filling the lawsuit at the Cirebon Kota Criminal Investigation Unit. But the performance of investigators in using the E-Manajemen Penyidikan is not optimal. This can be proven by the average number of Cirebon Kota Criminal Investigation Unit investigators who input the lawsuit which is less than the total number of Cirebon Kota Criminal Investigation Unit investigators. The author uses research literature and conceptual literature. The research library that serves as references are by Septyan Rangga Okky Saputra (2018) and Chrisvani Saruksuk (2019). The concept used is the concept of the National Police investigator, the concept of investigation management, and the concept of E-Manajemen Penyidikan. While the theory used is the theory of competence and the elements of management theory 6M by George R. Terry. The research method uses a qualitative approach whose results are strengthened by the results of interviews, observations, and document review results. The source of the research comes from primary and secondary data sources. Data validity uses triangulation. Data analysis techniques using data reduction, data presentation, and data withdrawal. The results found that the use of E-Manajemen Penyidikan in the Cirebon Kota Criminal Investigation Unit by improving investigator performance is highly dependent on the competence of the investigators which includes the knowledge, skills and attitudes of the investigators' behavior. From the research results, it can be seen that the performance of the investigators has not been maximized in management functions such as human resources, budget, facilities, infrastructure, methods, and marketing so that it becomes an inhibiting factor in the use of E-Manajemen Penyidikan. Based on the results of the study, the author advise leaders to carry out analysis and evaluation related to the use of E-Manajemen Penyidikan, provide rewards for active investigators, prepare the budget support needed in utilizing E-Manajemen Penyidikan, and establish Standard Operational Procedure (SOP) in using E-Manajemen Penyidikan.